Extração, hidrólise e remoção de fenilalanina das proteínas de farinha de arroz - Claudia Regina Vieira (2007)
EXTRACTION, HYDROLYSIS AND PHENYLALANINE REMOVAL FROM PROTEINS OF RICE FLOUR. The aim of this work was to use rice flour in the development of a new food whit low phenylalanine (Phe), to be used in phenylketonurics diet. Initially, different conditions of enzymatic extraction of proteins were compared, in order to optimize protein extraction yield (PEY). All the parameters investigated (enzyme type; temperature; pH; physical treatment of the sample; enzyme:substrate ratio (E:S) and initial concentration of raw material) affected PEY. The best result (PEY = 63.4%) was achieved for the initial concentration of raw material of 1:10 (w/v), with no physical treatment, pH 10.5, using an alkaline protease with E:S of 10:100, at 50 ºC. Then, the protein extract obtained under these conditions was hydrolysed using varying hydrolysis conditions and activated carbon (AC) as adsorbent for Phe removal. Some parameters such as enzyme type, E:S ratio, protein:AC ratio, type and mode of using of AC were evaluated. After passing the hydrolysates through the AC column, Phe was evaluated by second derivative spectrophotometry (SDS). The use of papain in a E:S of 4:100 and of the three types of AC in a protein:AC ratio of 1:88 showed to be efficient, and produced a hydrolysate with final Phe content (82.5 mg/100 g) which is bellow the maximum limit stated by the Brazilian legislation for products destined to phenylketonurics.